Analysis of a microbial community associated with polychlorinated biphenyl degradation in anaerobic batch reactors - Gomes, B. C.; Adorno, M. A. T.; Okada, D. Y.; Delforno, T. P.; Lima Gomes, Paulo Clairmont Feitosa de [UNESP]; Sakamoto, I. K.; Varesche, M. B. A. (Springer Nature, 2014)
The degradation of polychlorinated biphenyls (PCBs) was investigated under fermentativemethanogenic conditions for up to 60 days in the presence of anaerobic biomass from a full-scale UASB reactor. The low methane yields in the PCBs-spiked batch reactors suggested that the biomass had an inhibitory effect on the methanogenic community. Reactors containing PCBs and co-substrates (ethanol/ sodium formate) exhibited substantial PCB reductions from 0.7 to 0.2 mg mL-1 . For the Bacteria domain, the PCBs-spiked reactors were grouped with the PCB-free reactors with a similarity of 55 %, which suggested the selection of a specific population in the presence of PCBs. Three genera of bacteria were found exclusively in the PCB-spiked reactors and were identified using pyrosequencing analysis, Sedimentibacter, Tissierela and Fusibacter. Interestingly, the Sedimentibacter, which was previously correlated with the reductive dechlorination of PCBs, had the highest relative abundance in the RCS-PCB (7.4 %) and RCS-PCB-PF (12.4 %) reactors. Thus, the anaerobic sludge from the UASB reactor contains bacteria from the Firmicutes phylum that are capable of degrading PCBs.
Keywords: Co-substrate; Recalcitrant; Sedimentibacter; PCR-DGGE; 454 Pyrosequencing